Nano-sized SnO2 Photocatalysts: Synthesis, Characterization and Their Application for the Degradation of Methylene Blue Dye (Journal of Scientific Research, 2016)
In the present study, tin oxide (SnO2) nanoparticles were prepared by precipitation method using tin tetrachloride (SnCl4) as precursor and ammonia solution as precipitating agent followed by calcination at 400 ºC for 2 h. As-prepared SnO2 particles were characterized by X-ray diffraction (XRD) and Fourier Transform Infrared (FTIR). The powder XRD results revealed that the SnO2 nanoparticles had a typical tetragonal rutile (cassiterite) structure and the average crystallite size calculated by using the Debye Scherrer equation was found to be approximately 5.1 nm. The photocatalytic activity of the as-prepared photocatalysts was investigated by degrading methylene blue (MB) dye. The effect of pH, catalyst loading and initial dye concentration on photocatalytic degradation was investigated. Results showed that the SnO2 nanoparticles represented excellent photocatalytic activity for the degradation of MB under UV light with 200 min of irradiation time. The results also showed that the pH of solution had a direct influence on the photocatalysis process and basic pH was favorable for the degradation of MB. The effect of pH on photocatalytic activity was explained with the help of zero point charge (pHpzc). Furthermore, the photocatalysts could be easily recycled without significant change in the catalytic activity.